نظام اللّغة العربيّة العام والنّزوع نحو الارتقاء - البب إبراهيم; عبد الحليم فراس (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
إن النظام الإعرابي أوضح أنظمة العربية لذلك أولاه النحويون جلّ عنايتهم، ومهما يتوسع النظام فإنّه يقوم على مشابهة الأصل وحمل الكلام بعضه على بعض، وهو يتصف بالمرونة والتداخل. وقد اعتمد النّظام اللّغوي عند النّحاة القدامى بشكلٍ عامٍّ على محاكاة الاستعمال اللّغويّ، فهذا يتناسب مع المرحلة الأولى لتأسيس علم النّحو الّتي تستلزم الحذر والدّقّة في التّعامل مع الظّواهر النّحويّة، أمّا النّحاة المتأخّرون فقد تناولوا النظام اللغوي تناولاً عقلياً منطقياً، على شكل أركان: مقيس، ومقيس عليه، أو أصل، وفرع، وعلة جامعة سبب المشابهة، والحكم الذي هو وجه الشبه، وفرّعوا الأخيرين فروعاً كثيرة. غير أنّ نظام العربية ليس نظاماً عقلياً صرفاً، والنحو ليس قياساً كله، فهناك حيّزٌ للقياس، وهناك حيّزٌ للسّماع والاستعمال الفصيح الّذي لا يتّفق مع القياس العقليّ. ومن ثمّ كان للعدول عن القياس المجرّد في النّصّ القرآنيّ منطقه الخاصّ الّذي يرقى على المنطق العقليّ العامّ، ويتطلّب الارتقاء في تحليل البنية اللّغويّة لتلك الظّواهر وإعادة النّظر في تركيبها البنائيّ. The syntactic system is the clearest among Arab systems so grammarians gave it all their attentions. However, the system is based on imitating the original and making the words depend on each other. It is characterized by resilience and interference. According to the ancient grammarians, the syntactic system depends generally on imitating linguistic usage. This matches with the first stage of creating syntax which requires wariness and accuracy in dealing with syntactic phenomenon. However, late grammarians treat syntactic system in a rational, logical way. They deal with it in the shape of basic elements: measured, measured by, source, branch, combining elements which cause similarity, and the judging that’s considered the point of resemblance. Moreover, they divided the last two elements into many branches. The Arabic system is not a plain, rational system, and grammar is not all about measuring because there’s a space for measuring and a space for both hearing and eloquent usage which don’t match with rational measuring. There’s also a special area for deviation from abstract measuring in a koranic text, which exceeds the general rational logic, and demands ascension in analyzing lingual structure for that phenomenon and reconsidering their constructive structure.